Focal Nodular Hyperplasia-Like Lesions With Glypican-3 Positivity in Infancy. (January 2023) - Berklite, Lara; Shenoy, Archana; Hollowell, Monica; Fung, Bonita; Ranganathan, Sarangarajan
Purpose and Context: Glypican-3 is often used to discriminate between neoplastic and nonneoplastic liver. In focal lesions, positivity may be considered suggestive of a malignancy such as hepatoblastoma. However, glypican-3 is also normally expressed in the immature liver. We present a series of 5 cases of focal nodular hyperplasia (FNH)-like lesions arising in very young patients with glypican-3 expression and highlight the challenges these lesions present in the differential diagnosis of hepatoblastoma. Methods: Cases were obtained from the files of 3 tertiary pediatric hospitals. Clinical data were obtained from the electronic medical record and histopathologic material including immunohistochemical stains were reviewed. Key Results: Patients were aged 2 weeks to 6 months with peak AFP levels ranging from 88.6 to 204, 696 ng/mL. Microscopically, all were variably demarcated hepatocellular lesions with cords of hepatocytes, marked sinusoidal dilatation, and occasional fibrous bands and areas reminiscent of central scar with bile ducts. No significant cytologic atypia or increased mitotic activity were present. All showed glypican-3 expression and were negative for nuclear beta-catenin with intact reticulin framework. Conclusions: Our study highlights the pitfalls of evaluating focal liver lesions in infants when high AFP levels and glypican-3 expression may reflect immaturity rather than neoplasia.